2000
DOI: 10.1055/s-2000-8788
|View full text |Cite
|
Sign up to set email alerts
|

Zur prognostischen Relevanz der Proliferationsmarker Ki-67 (MIB 1), PCNA und p53 bei kombiniert chirurgisch und radiologisch therapierten Karzinomen des Oropharynx und der Mundhöhle

Abstract: Examination of Ki-67 is thought to provide useful prognostic information concerning squamous cell carcinomas of the oropharynx and oral cavity. Overexpression of p53 or PCNA status is not of prognostic value, which is consistent with earlier results. We conclude that the detection of Ki-67 is an unfavorable prognostic factor for squamous cell carcinoma of the oropharynx and oral cavity, at least if treated with a combination of surgery and postoperative irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…However, it was soon realised that PCNA is not at all proliferation specific, [15][16][17][18] and many studies revealed a poor correlation between this antigen and other proliferation markers, in addition to clinical parameters. [19][20][21][22] Consequently, PCNA staining is no longer recommended for use in surgical pathology. 20 23 24 During the past decade, several monoclonal and polyclonal antibodies against peptides from recombinant fragments of the Ki-67 antigen have been produced.…”
mentioning
confidence: 99%
“…However, it was soon realised that PCNA is not at all proliferation specific, [15][16][17][18] and many studies revealed a poor correlation between this antigen and other proliferation markers, in addition to clinical parameters. [19][20][21][22] Consequently, PCNA staining is no longer recommended for use in surgical pathology. 20 23 24 During the past decade, several monoclonal and polyclonal antibodies against peptides from recombinant fragments of the Ki-67 antigen have been produced.…”
mentioning
confidence: 99%
“…В трех исследованиях, включавших в общей сложности 192 пациента, наблюдался незначительный прогностический эффект этого маркера [11]. Напротив, исследование, проведенное Sittel C. et al [16] показало, что высокая экспрессия Ki 67 является неблагоприятным фактором в прогнозе течения и общей безрецидивной выживаемости.…”
unclassified